Genetic Features of Antarctic Acinetobacter radioresistens Strain A154 Harboring Multiple Antibiotic-Resistance Genes - Opazo-Capurro, Andrés; Higgins, Paul G.; Wille, Julia; Seifert, Harald; Cigarroa, Camila; González-Muñoz, Paulina; Quezada-Aguiluz, Mario; Domínguez-Yévenes, Mariana; Bello-Toledo, Helia; Vergara, Luis; González-Rocha, Gerardo (Frontiers in Cellular and Infection Microbiology, 2019)
While antibiotic-resistant bacteria have been detected in extreme environments, including Antarctica, to date there are no reports of Acinetobacter species isolated from this region. Here, we characterized by whole-genome sequencing (WGS) the genetic content of a single antibiotic-resistant Acinetobacter spp. isolate (A154) collected in Antarctica. The isolate was recovered in 2013 from soil samples at Fildes Peninsula, Antarctica, and was identified by detection of the intrinsic OXA-23 gene, and confirmed by Tetra Correlation Search (TCS) and WGS. The antibiotic susceptibility profile was determined by disc diffusion, E-test, and broth microdilution methods. From WGS data, the acquired resistome and insertion sequence (IS) content were identified by in silico analyses. Plasmids were studied by the alkaline lysis method followed by pulsed-field gel electrophoresis and conventional PCR. The A154 isolate was identified as A. radioresistens by WGS analysis and displayed >99.9 of similarity by TCS in relation with the databases. Moreover, it was resistant to ampicillin, ceftriaxone, ceftazidime, cefepime, cefotaxime, streptomycin and kanamycin. Likewise, in addition to the intrinsic blaOXA-23-like gene, A154 harboured the plasmid-encoded antibiotic-resistance genes blaPER-2, tet(B), aph(3’)-Via, strA and strB, as well as a large diversity of ISs. This is the first report of antibiotic-resistant A. radioresistens in Antarctica. Our findings show the presence of several resistance genes which could be either intrinsic or acquired in the region.